Sources of equality and inequality: Wages, jobs, households and redistribution - Lane Kenworthy (Luxembourg Income Study (LIS), 2008)
What are the principal sources of posttax-posttransfer inequality in affluent countries? To what extent do inequality of individual earnings, inequality of market household incomes, redistribution, and other factors influence the posttaxposttransfer income distribution? And what do the answers to these questions tell us about the best route to low posttax-posttransfer inequality? I explore these issues in a comparative fashion, focusing on the experiences of twelve countries - Denmark, Finland, Norway, Sweden, France, Germany, Italy, the Netherlands, Australia, Canada, the United Kingdom, and the United States - since the 1970s.
Keywords: 330; Einkommensverteilung; Lohn; Arbeitslosigkeit; Haushaltseinkommen; Familienbesteuerung; Einkommensumverteilung; OECD-Staaten